Status of some Trace Elements in Type-2 Diabetic Patients and its Relationship with Lipid Profile (Journal of Bangladesh Academy of Sciences, 2016)
Investigation of the serum level of copper, zinc, magnesium and manganese in type-2 diabetes mellitus and their possible association with lipid profile was carried out. The comparative study included 100 type-2 diabetic patients in Gr-II and 100 non-diabetic as control in (Gr-I). Results indicated that there is a significant lower level (p < .001) of serum Zn, Cu, Mg and Mn in diabetic patients compared with the control group, showing p value < .001. In type-2 DM patients (Gr-II) there were significant correlations between serum Zn and TAG (r = 0.209) and between Zn and HDL-C level (r = .199) showing p value